Comprehensive optimization of a diesel-E85 engine over the full operating range using the Taguchi method in intelligent charge compression ignition (ICCI) mode. (15th January 2023) - Zhang, Yaoyuan; Wu, Haoqing; Mi, Shijie; Zhao, Wenbin; He, Zhuoyao; Qian, Yong; Lu, Xingcai
Highlights: Taguchi method evaluates effect degrees of control parameters reducing calibration work. The upper limit of ITE is determined by engine load and speed. E85 ratio, injection strategy, and excess air ratio show a high impact on emissions. The peak ITE and the minimum NOx emissions are over 51 % and below 0.2 g/kWh. Abstract: Lean combustion engines have been regarded as applicable technologies meeting the stringent emission regulations, while control parameters of these engines have become more complex with the application of new technologies. The intelligent charge compression ignition (ICCI) engine was equipped with an additional direct injection system, further complicating the optimization process. To simplify the optimization of control parameters, Taguchi design of experiment was employed based on an L18 orthogonal array. The effect degree of various parameters including engine load, speed, excess air ratio, E85 (85 % ethanol and 15 % gasoline) energy ratio, and premixed strategies were investigated, while indicated thermal efficiency (ITE), particle number (PN), and gaseous emissions as responses were discussed using the signal-to-noise (S/N) ratio and the analysis of variance. An optimized control strategy of ICCI over full operating conditions was designed based on the rules obtained by the Taguchi method. It concluded that engine load and speed had a significant influence on the upper limit of ITE while excess air ratio, E85 energy ratio, and premixed strategies had varying degrees of effect on emissions. The optimized control strategy realized that the maximum E85 substitution ratio reached 80 %, reducing CO2 emission below 500 g/kWh in most conditions. The load range of ICCI combustion reached 75 % of the original diesel engine load (21 bar IMEP) considering engine mechanical strength and noise level, while the peak ITE and the minimum NOx emissions were over 51 % and below 0.2 g/kWh respectively under conditions of low speed and high load.